Hierarchical Advanced Tunneling Architectures for Scalable Distributed Artificial Intelligence - Raghavendra, Harish Kumar Chencharla (International Journal of Computing and Engineering, 2025)
Distributed artificial intelligence infrastructure faces mounting challenges as model complexity and size continue to expand exponentially. Traditional flat network architectures demonstrate significant inefficiencies at scale, resulting in degraded performance, excessive bandwidth consumption, and reliability concerns. This article introduces Hierarchical Advanced Tunneling Architecture (HATA), a novel network design that addresses these fundamental limitations through a structured, multi-layered approach. By organizing communication pathways according to data characteristics and traffic patterns, HATA enables more efficient resource allocation while maintaining global coordination. The architecture implements four distinct layers—Core, Distribution, Access, and Virtual Overlay—each optimized for specific communication requirements. When compared to traditional solutions, a thorough study shows significant gains in latency, throughput, and fault tolerance. The system also includes advanced cross-layer optimization, hierarchical caching, dynamic reconfiguration, and traffic classification algorithms. The architecture effectively manages heterogeneous hardware environments and addresses security considerations through multi-level protection mechanisms. These advancements establish hierarchical tunneling as a definitive paradigm for next-generation distributed AI infrastructure supporting the trillion-parameter frontier